Pengintegrasian Karakter pada Pembelajaran Tematik Terpadu di Sekolah Dasar - Muhammadi Muhammadi; Zainudin Abu Bakar (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2019)
This study aims to develop a model for integrating character education in integrated thematic learning in Indonesian elementary schools that is valid, practical and effective. Besides this research aims to see the differences in student characters between the control class and the experimental class. This research is a mixed method and development research (R&D) using 4-D steps. For this study, the one-group pretest and post-test one-group experimental time series design was used. The subject of the research was the second grade students of elementary school in Gadut Padang with 2 classes (IIB and IID). The results showed that the integration model of character education in integrated thematic learning that had been developed or fostered, as well as field trials through experiments were valid, practical, and effective. Specifically or specifically there is a significant difference in character between the control class and the experimental class when using the integration model of character education. Qualitatively the 4 characters that were developed look already entrenched from the application during the learning process.